Inumana intertestualità: appunti sulla citazione nelle Poesie della fine del mondo - Picconi, Gian Luca (Cuadernos de Filología Italiana, 2006)
Delfini’s way of writing is often tinged with intertextual quotations or allusions which prove to be functional within his work. In particular, the Poesie della fine del mondo, where the phenomenon acquires a status of unprecedented importance, are characterized by a kind of «teratology of quotation», which is peculiar to some Modernist texts. Intertextuality provides Delfini with a wide range of defensive as well as de-personalizing formulas, in a way akin to the more advanced contemporary poetry.